2019
DOI: 10.1136/emermed-2018-207807
|View full text |Cite
|
Sign up to set email alerts
|

Pressure induced skin and soft tissue injury in the emergency department

Abstract: The incidence of pressure ulcers or injuries is a global healthcare issue and in the top six most common adverse events in healthcare. Pressure injuries also are symptomatic of wider system failure and poor care. Recognition of these injuries and prevention strategies must start in the emergency department. This article will detail best practice in relation to both assessment of these injuries and their prevention in the emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 18 publications
0
15
0
14
Order By: Relevance
“…As for mask-related discomfort, we recommend wearing a properly fitted mask and applying moisturizer or gel beforehand for lubrication. 28 We recommend nonirritating products for handwashing, and applying adhesive bandages on the portions of the skin in contact with the mask to help reduce friction. Because of the possibility of conjunctival transmission of COVID-19—first reported by a Chinese expert 29 and later confirmed by scientific studies 30 —we strongly recommend using face shields in conjunction with goggles.…”
Section: Discussionmentioning
confidence: 99%
“…As for mask-related discomfort, we recommend wearing a properly fitted mask and applying moisturizer or gel beforehand for lubrication. 28 We recommend nonirritating products for handwashing, and applying adhesive bandages on the portions of the skin in contact with the mask to help reduce friction. Because of the possibility of conjunctival transmission of COVID-19—first reported by a Chinese expert 29 and later confirmed by scientific studies 30 —we strongly recommend using face shields in conjunction with goggles.…”
Section: Discussionmentioning
confidence: 99%
“…Then, IRAK1 and TRAF are released, and the latter combines with transforming growth factor β activated kinase-1 (TAK1) and induces its activation, then activates transcription factors NF- κ B and AP1 or activates JNK to act on AP1, and finally produces a large number of biological effector molecules, such as TNF- α and IL-8, IL-1 β [ 25 28 ]. Therefore, TLR2/MyD88/NF- κ B signaling pathway plays an important role in infectious diseases and inflammatory diseases [ 29 ], and inhibiting TLR2 could treat soft tissue infections by inhibiting inflammation and protecting tissues [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This research will be of great significance to the treatment of stress soft tissue injury. 8 According to the time of risk exposure in youth team sports, Soomro n's team determined the overall efficacy of structured multi-level IPPs integrating warm-up and neuromuscular strength, and conducted a systematic review and meta-analysis of the literature in multiple databases. The results showed that in 10 studies including 9 RCTs, the IRR of the composite population point estimate was 0.60.…”
Section: Related Workmentioning
confidence: 99%